Workshop On Integration of Digital Technology In Deep Learning Models For Elementary School Teachers: Lokakarya Integrasi Teknologi Digital Dalam Model-Model Pembelajaran Mendalam Untuk Guru Sekolah Dasar - Aan Yuliyanto; Tia Citra Bayuni; Fitriani Fitriani; Julia Anis Handayani; Candra Tri Utami; Winda Oktavia Amiri; Zakiyah Khairina Hani; Raihan Al Muabad; Irwan Hidayat (Bestari: Jurnal Pengabdian Kepada Masyarakat, 2026)
Abstrak The workshop aims to strengthen the competence of elementary school teacher in implementing in-depth learning through the integration of digital technology such as the Word wall platform, LearningApps and YouTube. This activity is a Community Service of Elementary School Teacher Education, Universitas Pelita Bangsa which involves elementary schools in the Wanajaya Cluster, Cibitung, Bekasi. Specifically, 27 teachers and 1 principal of SDN Wanajaya 3, and 4 students were involved in the training class on Integrating Digital Technology in Deep Learning Models. The workshop was carried out in three stages, the preparation stage where the community service team prepared the workshop offline by inviting several schools in Wanajaya to collaborate with the MoU and IA Cooperation. In the implementation stage, workshop participants participated in theoretical presentations and guided practice in using digital platforms to explore in-depth learning interactively, then evaluation was carried out via GForm. The evaluation results showed that 81% assessed that the presenter mastered the material very well, 82% assessed that the material was easy to understand, 83% assessed that the presenter actively involved the participants very well, 86% assessed that the material explanation strategy was very effective, and 88% assessed that the presenter stimulated participant discussion very well. The evaluation results showed that 81% assessed that the presenter mastered the material very well, 82% assessed that the material was easy to understand, 83% assessed that the presenter actively involved the participants very well, 86% assessed that the material explanation strategy was very effective, and 88% assessed that the presenter stimulated participant discussion very well. 86% of presenters were considered very good at managing time, 81% of presenters were considered very effective in using technology. 86% rated the speaker's attitude and interaction with participants as very good, 82% rated the material as relevant to the needs of elementary school teachers, 86% of participants were assessed as being able to provide real examples of classroom learning, 87% considered the workshop to be very useful, solution-oriented and innovative, 100% considered the in-depth learning workshop easy to follow and 55% of teachers found it easy to use YouTube, 35,7% Wordwall, 11% LearningApps, dan 8,5% Mentimeter. Thus, this in-depth learning workshop integrated with digital technology effectively improves teacher competency. Keywords: Workshop; Technology; Deep Learning; Elementary School Teachers Abstract This Workshop bertujuan menguatkan kompetensi Guru SD dalam implementasi pembelajaran mendalam melalui integrasi teknologi digital seperti platform Wordwall, LearningApps dan YouTube. Kegiatan ini merupakan Pengabdian Masyarakat PGSD Universitas Pelita Bangsa yang melibatkan SD di Gugus Wanajaya, Cibitung, Bekasi. Secara khusus yang mengikuti kelas pelatihan Integrasi Teknologi Digital dalam Model-model Pembelajaran Mendalam sebanyak 27 Guru dan 1 Kepala Sekolah SDN Wanajaya 3, dan 4 Mahasiswa yang dilibatkan. Workshop dilaksanakan melalui tiga tahapan, tahap persiapan tim pengabdian mempersiapkan workshop secara luring dengan mengajak kerjasama beberapa sekolah di Wanajaya dengan MoU dan IA Kerjasama. Tahap implementasi, peserta workshop mengikuti pemaparan teori dan praktik terbimbing dalam penggunaan platform digital untuk mengeksplorasi pembelajaran mendalam secara interaktif, kemudian pada evaluasi dilaksanakan via GForm. Hasil evaluasi 81% menilai pemateri menguasai materi sangat baik, 82% menilai materi mudah dipahami, 83% pemateri melibatkan secara aktif peserta sangat baik, 86% strategi penjelasan materi sangat efektif, 88% pemateri menstimulus diskusi peserta sangat baik. 86% pemateri dinilai sangat baik mengelola waktu, 81% Pemateri dinilai sangat efektif menggunakan teknologi. 86% menilai sikap dan interaksi pemateri terhadap peserta sangat baik, 82% menilai materi relevan dengan kebutuhan guru SD, 86% peserta dinilai mampu memberikan contoh nyata pembelajaran di kelas, 87% menilai Workshop yang dilaksanakan sangat bermanfaat, solutif dan inovatif, 100% menilai Workshop Pembelajaran Mendalam Mudah diikuti dan 55% Guru merasa mudah menggunakan YouTube, 35,7% Wordwall, 11% LearningApps, dan 8,5% Mentimeter. Dengan demikian workshop pembelajaran mendalam terintegrasi teknologi digital ini efektif meningkatkan kompetensi guru. Kata kunci: Workshop; Teknologi; Pembelajaran Mendalam; Guru Sekolah Dasar